N '-(5-Chloro-2-oxidobenzylidene-kappa O)-3-hydroxy-2-naphthohydrazidato-kappa N-2 ',O dimethyltin(IV) - Lee, S.M.; Ng, Seik Weng; Ali, Hapipah Mohd; Lo, K.M. (International Union of Crystallography, 2009)
The Sn-IV atom in the title compound, [Sn(CH3)(2)-(C18H11ClN2O3)], shows a trans-C2NO2Sn trigonal-bipyramidal coordination; the axial O-Sn-O angle is 155.22 (5)degrees. The tridentate N'-(5-chloro-2-oxidobenzylidene)-3-hydroxy2-naphthohydrazidate dianion is stabilized by an intramolecular O-H center dot center dot center dot N hydrogen bond.